Peningkatan Kualitas Permukiman Dengan Pendekatan Disain pada Bantaran Sungai Mergan di Kelurahan Kebonsari, Malang - Oktavi Elok Hapsari; Kusnul Prianto (Universitas Islam Negeri Sunan Ampel Surabaya, 2016)
The development of housing and settlement was not only intended for physical development but rather must be linked to the social, economic and cultural dimensions that support people's lives in a sustainable way. The settlement must provide environmental facilities for its citizens that accommodate the five basic elements; nature, people, society, places, and networks. The object studied was Kebonsari Village located on the southern border between Malang City and Malang Regency. Kebonsari village has an interesting topography because it is passed by two rivers, namely Mergan River and Sukun River which is located in eastern Kebonsari. However, a number of problems are encountered in Kebonsari urban village, including the unclean condition of Mergan River, poor condition of public facilities supporting settlements, such as arid and unkempt footpaths and lack of common space for residents. This study used a descriptive qualitative method with observational participatory technique.The outline of this study was the design concept of Mergan riverbank arrangement which includes the arrangement of paths and common space for the citizens who can improve the quality of settlements in Kebonsari urban village